Manager's theories about the process of innovation - Salaman, Graeme; Storey, John (2002)
Despite the widely-recognized importance of innovation to organizational competitiveness and national economic well-being, and despite the extensive commentary on the topic, the managerial processes which contribute to innovativeness and the factors and processes inhibiting its achievement remain underexplicated. This article contributes to an understanding of the management of innovation by approaching the innovation problem from an analysis of the accounts, interpretations and theories of the actors closely engaged with the process. Focusing on a large telecommunications equipment manufacturer, this article reveals how managerial discourse may hold the key to understanding the nature of the barriers to effective innovation. - Reproduced.
Keywords: Managers; Management